Sentidos das escolhas e do envolvimento ativista em organizações não governamentais internacionais - Barbosa, Marcos Antônio de Souza (2017)
Several organizations in the contemporary world act on causes considered to be of global concern, beyond the traditionally established formal boundaries of states and nations. International nongovernmental organizations – INGOs stand out in this field, which are linked to environmental, humanitarian and social development interests, because in recent years their operations have increased in number and complexity due to the increase in natural, biological, civil conflicts, wars and hunger, demanding an increasing number of people that are available, prepared and willing to participate in this universe: the activists. We made an analysis of the reasons that lead individuals to be attracted to a certain type of activist activity, applying an approach based on theoretical contributions from Psychoanalysis, specifically from Psychosociology, based on the assumption that activist action involves the interaction of complex, dense, ambivalent psychic processes, based on individual and collective desires and interests. The goal was to understand why individuals choose and engage with organizations linked to activism. In this sense, the proposal is a displacement from a purely descriptive study of activists’ occupation, work, profession and career to an analysis about the meanings of their performance. We interviewed 14 activists who had some type of relationship with these international organizations, regardless of their nationality and place of performance, in a research of qualitative and exploratory nature. From the Thematic Analysis, three themes emerged: a) The sharing of values; B) Being an activist and having a cause: 'That is how I am!'; C) Choices and their ambivalences. Our results highlight the importance of individual choices, the emphasis on group bonds and some tensions connected to being an activist.